Working temperature effects on mechanical integrity of cylindrical lithium-ion batteries. (July 2022) - Mo, Fuhao; Tian, Ye; Zhao, Siqi; Xiao, Zhi; Ma, Zhiling
Highlights: The influences of working temperatures on mechanical properties and short circuit of cylindrical lithium-ion cells were determined in compression and three-point bending. The working temperature presents negative correlations with the onset of short-circuit and mechanical properties of the cylindrical lithium-ion cells in compression loading. Non-significant effects of the working temperature on mechanical properties of the cylindrical lithium-ion cells were found in three-point bending. The short circuit criteria for a highly efficient FE battery cell modeling can be established based on internal stress in a specific direction. Abstract: The purpose of this study is to explore the influences of working temperatures on mechanical properties and the short circuit of cylindrical lithium-ion cells. A series of compression and three-point bending experiments of a typical 18, 650 cylindrical lithium-ion battery is implemented during the discharging process in different working temperatures. The experimental results show that the working temperature presents a negative correlation with the onset of short-circuit in compression loading but non-significant effects on mechanical properties in three-point bending. For the discharging rate, there are non-significant effects on mechanical properties and short circuits of battery cells in both bending and compression loading experiments. In summary, the working temperature effects cannot be neglected in cylindric lithium-ion battery failure, and combined simulation and experimental results indicate that the short circuit criteria for a highly efficient FE battery cell modeling can be established based on internal stress in a specific direction.